(untitled) (Tanzania Medical Journal, 2020)
Background Understanding characteristics of patients on second-line antiretroviral therapy (ART) in comparison to patients on first-line ART is important in addressing demographic and clinical issues related to treatment failure. Broad objective We aimed to compare characteristics of patients on second line ART to those of patients on first line ART and to assess factors associated with second line ART treatment in Dar es Salaam, Tanzania. Methodology Adult patients were systematically recruited in a cross sectional study from one primary level and one secondary level HIV clinics in Dar es Salaam Tanzania. Participants’ socio-demographic and clinical characteristics were recorded. Medians and interquartile ranges were used to compare continuous variables while proportions were used to compare categorical variables. Logistic regression was used to determine factors associated with second line ART treatment. Results We recruited 102 patients from each clinic. Compared to patients on 1st line ART, significantly more patients on second line ART were employed; 90.2% vs. 72.5%, p=0.001, had been on ART for ?60 months, 71.6% vs. 33.3%, p<0.001, had changed ART regimen ?3 times, 16.7% vs. 3.9%, p=0.003, presented with lower median (IQR) pre-ART CD4 counts 72 (26-192) vs. 150 (61-273) cells/µL respectively, p=0.03, had lower median (IQR) CD4 counts at the time of the study, 326(213-412) vs. 422 (299-583) cells/µL, p<0.001, had higher median (IQR) Creatinine; 0.9 (0.75-1.2) vs. 0.78 (0.66-0.9) mg/dl, p<0.001. Employment and being on ART for >60months were 2.5 and 4.4 times respectively more likely seen in patients on second line ART compared to first line ART, p<0.05. Conclusion and recommendation Majority of patients on second-line ART initiated ART with very low CD4 counts, had been on ART for more than sixty months and had changed their ART three times or more. They also had lower CD4 counts at the time of the study. Employment and duration of ART predicted likelihood of being on second-line ART. We recommend early screening for HIV and ART initiation before the immunity is severely compromised in order to reduce the burden of HIV treatment failure. Key words: First line antiretroviral therapy, Second line antiretroviral therapy, antiretroviral therapy resistance, HIV patients’ characteristics, Tanzania, ART adherence.